Perbaikan Instalasi Air Bersih Gedung Sekretariat Lembaga Pemberdayaan Masyarakat Kelurahan Telaga Sari - Miswaty, Miswaty; Widya, Widya (Abdimas Universal, 2025)
The community service activity in this article discusses efforts to improve clean water installation in the secretariat building of a community empowerment institution to enhance efficiency and service quality. Adequate clean water installation is crucial to support community empowerment activities but is often overlooked. Through infrastructure improvement and enhancement, this community services provides concrete solutions to address clean water supply issues in the secretariat building of the institution. The improvement method involves a comprehensive evaluation of the water pipe installation system, selection of HDPE pipe types, and appropriate implementation methods to minimize the potential for leaks. The application of this solution is expected to increase the availability and continuity of clean water, reduce maintenance burdens, and enhance water usage efficiency. The community service activity indicate that improving clean water installation in institutional buildings significantly enhances service quality and positively impacts the sustainability of community empowerment activities. These efforts align with sustainable development principles and can serve as a model for similar institutions to enhance basic infrastructure supporting community empowerment missions.